2020
DOI: 10.1002/ejp.1678
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor sensitizes nociceptors to C‐fibre selective supra‐threshold electrical stimuli in human skin

Abstract: BackgroundIntradermal injection of 1 µg nerve growth factor (NGF) causes sustained nociceptor sensitization. Slowly depolarizing electrical current preferentially activates C‐nociceptors.MethodsWe explored the differential contribution of A‐delta and C‐nociceptors in NGF‐sensitized skin using slowly depolarizing transcutaneous electrical current stimuli, CO2 laser heat, mechanical impact, and A‐fibre compression block. In 14 healthy volunteers, pain rating was recorded on a numeric scale at days 1–14 after NGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Slowly depolarizing transcutaneous electrical stimulation (4 Hz sinusoidal profile and 500 ms half sine wave pulses) induced burning pain in healthy subjects, activated primary afferent C-nociceptors, and revealed substantial accommodation upon continuous 4 Hz sinusoidal stimulation [ 15 , 17 , 18 ]. We found in our patients that about 50% reported enhanced pain upon 4 Hz sinusoidal stimulation of their stimulated neuropathic skin sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slowly depolarizing transcutaneous electrical stimulation (4 Hz sinusoidal profile and 500 ms half sine wave pulses) induced burning pain in healthy subjects, activated primary afferent C-nociceptors, and revealed substantial accommodation upon continuous 4 Hz sinusoidal stimulation [ 15 , 17 , 18 ]. We found in our patients that about 50% reported enhanced pain upon 4 Hz sinusoidal stimulation of their stimulated neuropathic skin sites.…”
Section: Discussionmentioning
confidence: 99%
“…The geometry of the electrodes and the temporal stimulation profile is critical for a selective activation of peripheral nerve fibers [ 10 14 ]. Slowly depolarizing transcutaneous currents of low-intensity with 4 Hz sinusoidal stimulation profile as well as single 500 ms half sine wave pulses can be used to stimulate nociceptors in human skin [ 15 18 ]. While single supra-threshold 500 ms half sine wave pulses induce a burst of action potentials, at 4 Hz sinusoidal stimulation single action potentials are evoked per sine wave [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty of matching stimulus configuration to the activated nerve fiber class, however, is rather unsatisfying. This issue can be addressed by employing slowly depolarizing electrical stimuli of halfsine and sine wave shape delivered transcutaneously via small punctate electrodes that selectively activate C-fibers (33)(34)(35)(36). Thereby, "polymodal" C-nociceptors are activated by a single 500 ms half-sine wave pulse responding with a current intensity dependent burst of action potential discharges (34).…”
Section: Electrically Evoked Itch In Healthy Human Subjectsmentioning
confidence: 99%
“…Expression changes in nerve fibers are particularly hard to detect in punch biopsies, as they make up only a minute amount of the tissue's total RNA, are not specifically targetable by current single cell transcriptomic approaches (76) and only refer to axonally transported RNA. These problems also preclude to link global transcriptomic changes to specific nerve fiber classes, which is particularly warranted, given that sinusoidal transcutaneous electrical stimuli preferentially activate C-fibers (35,36). However, despite these technical difficulties, one study found the voltage-gated sodium channels Nav1.3, Nav1.7, and Nav1.9 to be overexpressed in eczematous skin of AD patients and, importantly, this overexpression correlated with pruritus severity (72).…”
Section: Parameters Influencing Electrical Nerve Fiber Activation In the Skinmentioning
confidence: 99%
“… 57 Particularly, the C-polymodal nociceptors are further categorized as mechano-heat-responsive units and mechano-insensitive units (CMi) according to the different electrical thresholds. Past studies suggested CMi became sensitized by tissue damage (ie, skin denervation), 130 nerve growth factor (NGF), 113 , 114 , 141 and capsaicin administration. 140 Therefore, the neuropathology of skin denervation provided a basis for evaluating the alteration of pain perception.…”
Section: Introductionmentioning
confidence: 99%